« Ils sont du décor qui bouge » : corps « plastiques » en scène - CLÉREN, Marie (Studia Universitatis Babeș-Bolyai Dramatica, 2015)
«They are Moving Décor»: «Plastic» Bodies on Stage. In the XX century, many painters collaborate on theater plays or ballets bringing a new « plastic » dimension on stage. Whether in Skating Ring from Canudo ou La Création de monde from Cendrars, in Parade from Cocteau or Coucou Bazar from Jean Dubuffet, characters wear suits that make them look like hybrid creatures and turn them into elements of the setting. Colors and chosen patterns integrate them to those «animated» pictures and raise the question of the future of the actor’s body in such performances. We can wonder if the implication of painters on stage has consequences on acting or choreography. Dubuffet, for exemple, advocates slowness in a theater of the body that owes Artaud’s theory. Léger, on the other hand, claims objects life and describes the dancers as «mobile decors». That breeds a mechanical play very close to Charlie Chaplin. In this way, collaboration between painters and poets lead to a change of the body’s status on stage. This change is something that we can relate to: it becomes, in these kaleidoscopic shows, the piece of a puzzle that the eye of the spectator has to reconstitute. Having studied the metamorphoses of the body of the actor under the brush of famous painters, we can see the consequences of these transformations on the game of the one who becomes "figure" (Dubuffet) or "dancer-machine" (Schlemmer). Pull what the constraints compulsory for the body on the direction of these "alive paintings"?